Combined factor IIa and Xa inhibitor therapy for thrombosis whilst on therapeutic anticoagulant. Issue 143 (July 2016) - Arachchillage, Deepa R.J.; Besser, Martin; Maclean, Rhona; Baglin, Trevor; van Veen, Joost J.
Highlights: Low molecular weight heparin (LMWH) is the treatment of choice in cancer related VTE. Managing cancer related recurrent VTE on therapeutic anticoagulation is a challenge. Current guidelines recommend dose escalation of LMWH with ant-Xa monitoring. Combined factor Xa _amp_amp; factor IIa inhibitors may be an option in refractory thrombosis.